Profile of Cultural Humility in College Students - Subhi, Muhamad Rifa’i (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
This study aims to describe the profile of cultural humility in the students. The scope of this study includes the positive characteristic characteristics, and negative characteristic reflecting superiority and making assumptions. The results of the study indicate that the profile of cultural humility in each student can not be separated from activities or activities in everyday life. This shows that cultural humility is an ability that is not automatically owned by individuals. A special development program is required for cultural humility to be mastered well by potential counselors. One of these is the personal humility development guidance program. Through the guidance program is expected to grow cultural humility which eventually can be obtained endpoint of cultural humility in the form of the character of flexibility or humility of the individual when interacting with others.